P L S N A J U T R O !!! ​



P L S N A J U T R O class=

Odpowiedź :

Krysia

[tex]11a)\\\\ \frac{3}{4}+ \frac{2}{3}:(- \frac{12}{8})+(1\frac{1}{2})^2=\frac{3}{4}+ \frac{\not{2}^1}{3}*(- \frac{8}{\not{12}^6})+( \frac{3}{2})^2=\frac{3}{4} - \frac{8}{18} + \frac{9}{4} = \frac{27}{36} - \frac{16}{36} + \frac{81}{36} =\\\\=\frac{11}{36}+\frac{81}{36} =\frac{92}{36}=\frac{23}{9}=2\frac{5}{9}\\\\b)\\\\ \frac{(2- \frac{1}{7})*3}{2+0,6} - 8* \frac{3}{7}=\frac{( \frac{14} {7}- \frac{1}{7})*3}{2+ \frac{6}{10}} - \frac{24}{7}=\frac{ \frac{13} {7} *3}{2+ \frac{3}{5}} - \frac{24}{7}=\frac{ \frac{39} {7} }{2\frac{3}{5}} - \frac{24}{7}=\\\\\\=\frac{39}{7}:\frac{13}{5} -\frac{24}{7} =\frac{\not{39}^3}{7}*\frac{5}{\not{13}^1} -\frac{24}{7} =\frac{15}{7}-\frac{24}{7}=-\frac{9}{7}=-1\frac{2}{7}[/tex]

[tex]c)\\\\ (\frac{1}{3}+ \frac{2}{7} ):(1- \frac{1}{9}) + \frac{3}{7}=(\frac{7}{21}+ \frac{6}{21} ): \frac{8}{9} + \frac{3}{7}= \frac{13}{\not{21}^7}* \frac{\not(9)^3}{8} + \frac{3}{7} =\\\\= \frac{39}{56} +\frac{3}{7}= \frac{39}{56} +\frac{24}{56}=\frac{63}{56}=\frac{9}{8}=1\frac{1}{8}\\\\d)\\\\ (\not{2}^1* \frac{5}{\not{6}^3})^2-(3^2- \sqrt{1\frac{7}{9}})= ( \frac{5}{3})^2-(9- \sqrt{ \frac{16}{9}})= \frac{25}{9}-(9-\frac{4}{3})=\frac{25}{9}-( \frac{27}{3}-\frac{4}{3})=\\\\\\=\frac{25}{9}- \frac{23}{3}=\frac{25}{9}- \frac{69}{9}=-\frac{44}{9}=-4\frac{8}{9}[/tex]

[tex]e)\\\\\left [ (- \frac{2}{3})^2:\frac{8}{9} \right ] -(\frac{3}{4}-1\frac{1}{8})=\left [ \frac{\not{4}^1}{\not{9}^1}*\frac{\not{9}^1 }{\not{8}^2} \right ]^2 -(\frac{6}{8}- \frac{9}{8})=( \frac{1}{2})^2-(-\frac{3}{8})= \frac{1}{4}+\frac{3}{8}=\\\\\\=\frac{2}{8}+\frac{3}{8}=\frac{5}{8}\\\\f)\\\\ 1,6* \frac{7}{16} - \frac{2,7}{3^3} - \frac{5*0,7}{0,35}= \frac{\not{16}^1}{10}* \frac{7}{\not{16}^1} - \frac{2,7}{27} - \frac{3,5}{0,35}= \frac{7}{10} - 0,1- 10=\\\\\\=0,7-10,1=- 9,4[/tex]